Statistical analysis of factors influencing student buying behaviour towards online shopping using multiple linear regression analysis / Norshaieda Abdullah ... [et al.] - Abdullah, Norshaieda; Suhaimi, Suzainiwati; Che Kamaruzaman, Noor Azlem; Mohd Zaki, Nurul Aisya Fatiera (Unit Penerbitan, UiTM Kelantan, 2022)
This paper is a study about Universiti Teknologi MARA (UiTM) Kota Bharu students' buying behaviour towards online shopping during the COVID-19 pandemic. This study is conducted to identify significant factors that influence students' buying behaviour towards online shopping during pandemic. 307 undergraduates in UiTM Kota Bharu were taken as samples using Stratified Probability Sampling technique. Then, direct questionnaires were distributed to all of them and the data were analysed using Statistical Package for the Social Sciences (SPSS). This study found that the relationship between convenience and product variety on students' buying behaviour towards online shopping has a strong positive linear relationship. However, time and trust have a weak positive relationship. The Multiple Linear Regression analysis shows that convenience and product variety are significant factors that influence students' buying behaviour. As a recommendation, future researchers should add more factors to be studied as well as the number of items for each factor in the questionnaire.